2022
DOI: 10.1186/s12889-022-12830-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on Bordetella pertussis infections in England

Abstract: Background In March 2020, England went into its first lockdown in response to the COVID-19 pandemic. Restrictions eased temporarily, followed by second and third waves in October 2020 and January 2021. Recent data showed that the COVID-19 pandemic resulted in reduced transmission of some invasive diseases. We assess the impact of the COVID-19 pandemic on pertussis incidence and on the immunisation programme in England. Methods We assessed trends in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…The observed decrease in B. pertussis was 88% in our study, whereas the English study presented a decrease of 97%, but the detection rates in this study were relatively rare (only 21 detections in 2021), so these findings were practically similar [ 7 ]. The results of this study are also similar to the previous reports regarding the decrease in the detections of M. pneumoniae [ 8 11 ].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The observed decrease in B. pertussis was 88% in our study, whereas the English study presented a decrease of 97%, but the detection rates in this study were relatively rare (only 21 detections in 2021), so these findings were practically similar [ 7 ]. The results of this study are also similar to the previous reports regarding the decrease in the detections of M. pneumoniae [ 8 11 ].…”
Section: Discussionsupporting
confidence: 49%
“…A previous study from England reported a 98% reduction in Bordetella pertussis detections among infants (age less than 1 years) [ 7 ]. A study from Israeli found that the rates of B. pertussis and Mycoplasma pneumoniae decreased in hospitalized patients with respiratory tract infections during the early months of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…While the estimated rate of recent infection in this study was lower than that in a previous study in Zhejiang during September and October 2014 [20] . This discrepancy might be influenced by the pandemic COVID‐19 as many strict prevention and control measures were implemented in 2020, which may reduce the circulation of pertussis bacteria [33] . In addition, since pertussis was a cyclic disease, the downward trend always come after the peak of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…No concurrent SARS-CoV-2 cases were detected. Prenatal pertussis prevalence was 2.7% lesser in 2020-2021 [84] .…”
Section: Latest Studiesmentioning
confidence: 89%